Chrysanthemum CmWRKY53 negatively regulates the resistance of chrysanthemum to the aphid Macrosiphoniella sanborni. (1st July 2020) - Zhang, Wanwan; Gao, Tianwei; Li, Peiling; Tian, Chang; Song, Aiping; Jiang, Jiafu; Guan, Zhiyong; Fang, Weimin; Chen, Fadi; Chen, Sumei
Abstract: Chrysanthemum is frequently attacked by aphids, which greatly hinders the growth and ornamental value of this plant species. WRKY transcription factors play an important role in the response to biotic stresses such as pathogen and insect stresses. Here, chrysanthemum CmWRKY53 was cloned, and its expression was induced by aphid infestation. To verify the role of CmWRKY53 in resistance to aphids, CmWRKY53 transgenic chrysanthemum was generated. CmWRKY53 was found to mediate the susceptibility of chrysanthemum to aphids. The expression levels of secondary metabolite biosynthesis genes, such as peroxidase- and polyphenol oxidase-encoding genes, decreased in CmWRKY53 -overexpressing ( CmWRKY53 -Oe) plants but dramatically increased in chimeric dominant repressor ( CmWRKY53 -SRDX) plants, suggesting that CmWRKY53 contributes to the susceptibility of chrysanthemum to aphids, possibly due to its role in the regulation of secondary metabolites.